1999
DOI: 10.1007/pl00006623
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Changes in Excretion of Persistent Organochlorine Compounds with Human Breast Milk on Related Exposure of Breast-Fed Infants

Abstract: This study was an attempt to identify if there are any trends in excretion of 1,2,3,4,5,6-hexachlorocyclohexane (HCH) isomers alpha-, beta-, and gamma-, hexachlorobenzene (HCB), [1,1,1-trichloro-2, 2-bis(4-chlorophenyl)ethane] (p,p'-DDT), [1,1-dichloro-2, 2-bis(4-chlorophenyl)ethane] (p,p'-DDD), [1,1-dichloro-2, 2-bis(4-chlorophenyl)ethylene] (p,p'-DDE), and polychlorinated biphenyls (PCBs) with human milk during lactation. The shortest lactation studied took 16 weeks, and the longest 84 weeks. Three hundred f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Apart from valuable nutrients, the fi sh may also contain chloroorganic pollutants such as polychlorinated biphenyls that accumulate in human adipose tissue. Their levels in human adipose tissue in Poland were similar to those reported for industrialized nations of Western Europe [Loganathan et al, 1993;Czaja et al, 1999] and averaged 1500 ng/g lipids. Recent studies have indicated that the exposure to contaminants, such as PCBs, may cause disruption in reproductive function, and contribute to neurobehavioral and developmental defi cits in newborns and young children [Sager, 1983;Courval et al, 1996;Yang et al, 2005].…”
Section: Introductionsupporting
confidence: 81%
“…Apart from valuable nutrients, the fi sh may also contain chloroorganic pollutants such as polychlorinated biphenyls that accumulate in human adipose tissue. Their levels in human adipose tissue in Poland were similar to those reported for industrialized nations of Western Europe [Loganathan et al, 1993;Czaja et al, 1999] and averaged 1500 ng/g lipids. Recent studies have indicated that the exposure to contaminants, such as PCBs, may cause disruption in reproductive function, and contribute to neurobehavioral and developmental defi cits in newborns and young children [Sager, 1983;Courval et al, 1996;Yang et al, 2005].…”
Section: Introductionsupporting
confidence: 81%
“…mers, was detected in 9 samples at relatively high concentrations, as most of them contained more than 200ngg 1. The reason could be related with the fact that the excretion of the J3 isomer from the human body takes five times longer than for other HCH isomers, and that the J3-HCH ability to accumulate in tissue fat is from 10 to 30 times greater than for other isomers [16]. The amount reported for this compound in human and animal tissue from different regions of the world is usually in the same range of concentration as those found in this paper [6,15,22,26].…”
Section: Application Of the Procedures To Human Adipose Tissue Samplesmentioning
confidence: 61%
“…Our finding might be consistent with reverse causality as well in that women with endometriosis tend to have lower parity and, thereby, fewer opportunities to breastfeed. Since breastfeeding is reported to lower women's serum concentrations of OCPs [29, 30], higher concentrations may simply reflect less breastfeeding and not causality, per se . We purposefully did not include gravidity or parity in the model, since they are likely to be in the endometriosis pathway.…”
Section: Discussionmentioning
confidence: 99%